Opportunities and Competition in Thick Labor Markets: Evidence from Plant Closures - Peter Haller; Daniel F. Heuermann (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Since Marshall (1890), it has been widely held in urban economic theory that cities ensure workers against the risk of unemployment by offering a larger pool of potential jobs. Using a large administrative panel data set on workers affected by firm closures, we examine whether positive effects from a higher urban job density are offset by more intense competition between workers. When controlling for the sorting of workers between regions, we find no evidence that the number of days workers spend in unemployment decreases with local job density. Instead, longer unemployment periods in cities are partly driven by more intense competition for available jobs
Keywords: J63; J64; R12; R23; 330; agglomeration; thick labor markets; displacement